Peningkatan organizational citizenship behavior pada Aparatur Sipil Negara generasi milenial - Diah Pranitasari; Arini Mustikaningrum Kasaluri Kusumaningtyas (Jurnal STEI Ekonomi, 2023)
This research aims to determine the influence of organizational culture and employee engagement on organizational citizenship behavior with job satisfaction as a mediating variable among Millennial Civil Servants. It is a quantitative study with organizational culture and employee engagement as independent variables, and job satisfaction and organizational citizenship behavior as dependent variables. The research was conducted on Civil Servants at the Supreme Audit Agency (BPKP), with a total population of 5,901 Civil Servants. The study is limited to Millennial Civil Servants, with a total of 3,428 individuals. Using purposive sampling, which includes Civil Servants who have been working for more than 3 years, the sample size is determined using the Slovin formula, resulting in a sample of 358 Civil Servants. Data were collected through the distribution of questionnaires to Civil Servants, and the data were processed using smartPLS software. The research findings can be summarized as follows: organizational culture influences job satisfaction; organizational culture does not affect organizational citizenship behavior; employee engagement influences organizational culture; employee engagement influences organizational citizenship behavior; organizational culture does not affect organizational citizenship behavior through job satisfaction; employee engagement does not affect organizational citizenship behavior through job satisfaction. Note: This article serves as a restored version of the original content following a corruption incident. The Digital Object Identifier (DOI) has been successfully re-registered and reactivated to ensure continued accessibility and citation integrity.